A systematic review of household energy transition in low and middle income countries. (April 2022) - Guta, Dawit; Baumgartner, Jill; Jack, Darby; Carter, Ellison; Shen, Guofeng; Orgill-Meyer, Jennifer; Rosenthal, Joshua; Dickinson, Katherine; Bailis, Rob; Masuda, Yuta; Zerriffi, Hisham
Abstract: The use of solid fuels stoves contributes to a range of adverse health and social outcomes and can impact regional and global climate. Reducing these impacts requires both adoption and use of cleaner energy solutions and reduction or elimination of solid fuel use. Decades of improved stove and fuel programs in the developing nations have achieved only limited success in fully or even partially replacing solid fuel stoves, highlighting the challenges of modernizing energy. In this paper, we provide a systematic review to characterize household decision-making and the factors that influence adoption and disadoption of both cleaner fuels and improved biomass stoves, and use and suspension of solid fuels. We searched key bibliometric databases and then screened, appraised, and synthesized 92 studies. These were categorized into seven broad household cooking fuel/stove adoption and suspension decision-making: adoption, adoption and suspension, fuel choice, expenditure, level of fuel use, use and non-use decision, and others. We then use these studies to provide a detailed account of factors that influence household cooking fuel/stove adoption and suspension decisions under seven domains (technological characteristics, demographic, socioeconomic, market development, institutional, biophysical). Based on our review results we developed a conceptual framework of the dynamic decision-making process in household energy use decisions and the factors influencing them. Given that households can use multiple fuels and technologies (stove stacking), an understanding of household energy transitions requires attention to both the adoption and use of new fuels but also the reduction in use or suspension of solid fuels and stoves.